Exploring Students’ Cognitive Pathways in Understanding Statistical Variability in Digital Learning Environments - Hidayah, Nida'ul (PT FORMOSA CENDEKIA GLOBAL, 2026)
Understanding statistical variability is a core competency in technology education and data literacy, particularly in digitally mediated learning environments that demand advanced cognitive processing. This exploratory qualitative study investigates students’ cognitive pathways in constructing understanding of statistical variability through interactions with digital, technology-based tasks. Using a Think-Aloud Protocol supported by screen recordings, data were collected from 12 students at a public senior high school in Bandung, West Java, and analyzed using Cognitive Task Analysis. The findings reveal multi-layered cognitive pathways, beginning with the identification of visual elements, followed by exploration of data changes, and progressing toward meaning construction and interpretation of variability. Difficulties emerge at the stage of integrating concepts, especially when students must connect dynamic visual data with abstract statistical interpretations. The study contributes to theoretical insights into students’ cognitive structures in digital learning contexts and offers practical implications for designing adaptive, technology-based instructional strategies aligned with learners’ thinking processes.